SOCIAL AND CULTURAL MARKETING IN THE DEVELOPMENT OF FAMILY LEISURE CULTURE (Scientific journal of the Fergana State University, 2023)
The article examines the concept, essence and specifics of marketing in the socio-cultural sphere. The authors cite the main trends of the digital world, which have a significant impact on the role of socio-cultural marketing in the development of family leisure in Uzbekistan. It studies foreign methods and offers suggestions for their implementation in our country. It also analyzes the issues of marketing and raising the spiritual and cultural level of the public through the provision of modern creative services in the field of culture and arts. The article provides analytical conclusions on the prospects of the social and cultural market in the development of family recreation.